2016
DOI: 10.17221/206/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Origin and distribution of the brachial plexus in the Spix's yellow-toothed cavy (Galea spixii Wagler, 1831) (Rodentia, Caviidae)

Abstract: Due to the absence of literature on the brachial plexus in the Spix's yellow-toothed cavy, this study was conducted to examine the origin and neural distribution of this rodent's brachial plexus. Ten adult animals obtained from previous experiments were thawed, fixed in 10% formalin solution for 72 h and then dissected. Cotton blocks soaked in 2% hydrogen peroxide were placed on the ventral roots of the plexus. Photographs of the most representative specimens were taken and schematic sketches were prepared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 17 publications
4
13
2
Order By: Relevance
“…The suprascapular nerve had as its most frequent origin the branches C 4 and C 5 , and its nervous territory consists of the supraspinal and infraspinal muscles, differing from that described by Guimaraes et al (2013) when studying the plexus in the nutria and by Aydin (2003) in the thorn hog where the roots C 5 and C 6 were described. These results also differ from our previous study in Spix's yellow-toothed cavy (Araujo Jr et al 2016), where we found that it emerges from C 6 and C 7 . The C 6 or C 7 branches do not participate in the formation of this nerve in the gerbil.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The suprascapular nerve had as its most frequent origin the branches C 4 and C 5 , and its nervous territory consists of the supraspinal and infraspinal muscles, differing from that described by Guimaraes et al (2013) when studying the plexus in the nutria and by Aydin (2003) in the thorn hog where the roots C 5 and C 6 were described. These results also differ from our previous study in Spix's yellow-toothed cavy (Araujo Jr et al 2016), where we found that it emerges from C 6 and C 7 . The C 6 or C 7 branches do not participate in the formation of this nerve in the gerbil.…”
Section: Discussioncontrasting
confidence: 99%
“…Scavone et al (2008) reported in the spotted paca the origin of this nerve only from C 6 , while Gamba et al (2007) in the chinchilla describe the origin in C 6 and C 7 , differing from what is observed in the gerbil. The cranial pectoral nerve is similar to that found in rats (Greene 1963), emerging from C 5 and C 6 , and it is different in the nutria (Guimaraes et al 2013), which emerges solely from C 6 , in Spix's yellow-toothed cavy (Araujo Jr et al 2016), in which both nerves are formed by C 6 and C 7 and also in the chinchilla (Gamba et al 2007) where it is formed only from C 7 .…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations